EFEKTIFITAS DAN KONTRIBUSI PENERIMAAN PAJAK DAERAH TERHADAP PENDAPATAN ASLI DAERAH PADA PEMERINTAHAN KABUPATEN PAMEKASAN - Salehoddin, Salehoddin (JURNAL AKUNTANSI DAN INVESTASI, 2019)
The purpose of this study is to measure the extent of effectiveness of local tax revenue in Pamekasan Regency and measure how the contribution of regional taxes to Regional Original Revenues in Pamekasan Regency. This study uses quantitative descriptive methods. The results of this study are the effectiveness of local taxes from 2015-2017 on average is very effective with an average percentage of 126.22%. This can be seen from the local tax target. The results of the percentage of effectiveness from 2015 amounted to 118.83% in 2016 amounted to 122.43% and in 2017 amounted to 134.98%. and The level of contribution of Pamekasan district tax revenue from 2015-2017 is less able to make a good contribution. Because in 2016 and 2017 decreased with the percentage in 2015 amounted to 13.59% and in 2016 amounted to 15.09% and in 2017 amounted to 14.40% which was caused by increasing the realization of regional original income each year